1994
DOI: 10.1056/nejm199409013310903
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Medically Treated Patients with Homozygous β-Thalassemia

Abstract: The prognosis for survival without cardiac disease is excellent for patients with thalassemia major who receive regular transfusions and whose serum ferritin concentrations remain below 2500 ng per milliliter with chelation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
555
5
17

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 812 publications
(598 citation statements)
references
References 23 publications
21
555
5
17
Order By: Relevance
“…Median serum ferritin levels in both patient groups at month 24 were lower than the threshold of 2500 ng/mL, which is associated with increased morbidity and mortality [22,23]. In parallel, mean LIC was reduced to below the threshold of 15 mg Fe/g dw by month 24, indicating a substantial reduction in iron burden (from baseline values above 30 mg Fe/g dw; considerably higher than in other monotherapy and combination therapy studies [9,10]) and a reduced risk of progressive organ damage and early death [24,25].…”
Section: Discussionmentioning
confidence: 83%
“…Median serum ferritin levels in both patient groups at month 24 were lower than the threshold of 2500 ng/mL, which is associated with increased morbidity and mortality [22,23]. In parallel, mean LIC was reduced to below the threshold of 15 mg Fe/g dw by month 24, indicating a substantial reduction in iron burden (from baseline values above 30 mg Fe/g dw; considerably higher than in other monotherapy and combination therapy studies [9,10]) and a reduced risk of progressive organ damage and early death [24,25].…”
Section: Discussionmentioning
confidence: 83%
“…The greater the body iron burden, the greater the risk of cardiac disease. One study in thalassaemia major patients found that those with at least two-thirds of serial serum ferritin estimations less than 2,500 mg/L had significantly less cardiac disease than those with higher levels [10]. Brittenham et al [11] studied 59 thalassaemia major patients who were more than 7 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin is the most frequently used measure as it is inexpensive, widely available, and reliable, with extensive clinical validation in monitoring iron status. Ferritin measurements have prognostic value, as demonstrated by recent studies, one of which identified cardiac-related mortality greater than 80% over 15 years among patients with thalassemia in whom more than 67% of ferritin measurements exceeded 2,500 ng/mL [6,7]. However, in individuals the predictive value of ferritin is limited by inflammation and vitamin C deficiency.…”
Section: Serum Markers Of Iron Statusmentioning
confidence: 97%